The association between chronic renal failure and renal cell carcinoma may differ between black and white Americans - Hofmann, Jonathan N (2012)
PURPOSE: In the United States, renal cell carcinoma (RCC) incidence is higher among blacks than among whites. Risk of RCC is elevated among end-stage renal disease patients, although no studies have looked at differences by race in the relationship between chronic renal failure and RCC. METHODS: We investigated RCC risk in relation to chronic renal failure in a population-based case-control study of blacks and whites in Chicago and Detroit. Data, including information on kidney disease, were collected from interviews with 1,217 RCC cases (361 blacks, 856 whites) and 1,235 controls (523 blacks, 712 whites). Odds ratios (OR) and 95% confidence intervals (CI) were estimated using unconditional logistic regression. RESULTS: Risk of RCC was increased in relation to chronic renal failure (OR 4.7, 95% CI 2.2–10.1) and dialysis (OR 18.0, 95% CI 3.6–91). The association remained after defining exposure as those who had chronic renal failure ≥10 years prior to RCC diagnosis. Chronic renal failure was more strongly associated with RCC among blacks than among whites (OR 8.7, 95% CI 3.3–22.9 and 2.0, 0.7–5.6 respectively; P(interaction)=0.03) and among those without a history of diabetes relative to diabetic subjects (OR 8.3, 95% CI 3.1–22.7 and 1.9, 0.6–5.9 respectively; P(interaction)=0.03). CONCLUSIONS: These results suggest that chronic renal failure is a strong risk factor for RCC, particularly among black and non-diabetic subjects. Our findings of differences in risk estimates by race, to our knowledge the first such report, require replication.